Pengaruh Tabungan Wadiah, Pembiayaan Bermasalah (NPF) dan Risiko Likuiditas (FDR) Pada Produk ‘Tepat Pembiayaan Syariah’ Terhadap Profitabilitas (ROA) PT. Bank BTPN Syariah Tbk (2015 – 2023) - Dewi, Aulia Siska Puspita; Anwar, Moch Khoirul; Badrul Munir, Maryam Bte (El-Qist: Journal of Islamic Economics and Business (JIEB), 2024)
This study aims to investigate the influence of waḍī‘ah savings, Non-Performing Financing (NPF), and Financing to Deposit Ratio (FDR) on the profitability (Return on Assets/ROA) of PT. Bank BTPN Syariah Tbk, focusing on its flagship product, Tepat Sharia Financing, over the period 2015–2023. Employing an associative quantitative approach, the research utilizes secondary quarterly financial data analyzed through multiple linear regression using EViews 12. The results demonstrate that waḍī‘ah savings have a significant positive effect on profitability, while both NPF and FDR exert significant negative effects on ROA. The model explains 75.91% of the variation in profitability. These findings highlight the critical role of liquidity management and credit risk control in ensuring the sustainability of Islamic microfinance-focused banks. The key contribution of this study to the international Islamic banking literature lies in its empirical evidence from a microfinance-driven Islamic bank model, which remains underexplored globally. It underscores how tailored savings products combined with responsible risk management can enhance financial performance, offering valuable insights for Islamic banks operating in emerging economies with similar socio-economic contexts.